SUPPLIER PERFORMANCE ASSESSMENT USING ANALYTICAL HIERARCHY PROCESS METHOD - Dana Santoso; Arif Mahendra Besral (SINERGI, 2018)
This research was conducted in Hyundai Aluminium Co., Ltd. The company is a manufacturer and applicator for the job, especially aluminium curtain wall installation. Glass materials needed to form a curtain wall unit that these materials are not produced by Hyundai Aluminium Co., Ltd. To the researchers intend to determine the priority criteria, sub-criteria and consistency of thought or opinion of the respondents who are staff at Hyundai Aluminium Co., Ltd. in determining the glass supplier. In this study, the authors use the method of Analytical Hierarchy Process (AHP) to determine the priority of criteria, sub-criteria that compared global priority and will test the level of consistency of answers. The order of importance of criteria on the results of this research is Quality (.290), accuracy of delivery (0.279), price (0.238) and Service (0.193). Sequence global priority sub-criteria are H1 (0.174), K1 (0,138), D1 (0.114), K3 (0.096), H2 (0.063), K2 (0.056), L3 (0.034), D2 (0.025), L2 (0,023), L1 (0.006). Consistensi Value Ratio (CR) among criteria and sub-criteria inter smaller than 0.1 (CR, 0.1) which means that the answers of the respondents consistently.